Institutions, Opportunism and Prosocial Behavior: Some Experimental Evidence - Antonio Cabrales; Irma Clots-Figueras; Roberto Hernán-González; Praveen Kujal (Institute of Labor Economics (IZA), 2020)
Formal or informal institutions have long been adopted by societies to protect against opportunistic behavior. However, we know very little about how these institutions are chosen and their impact on behavior. We experimentally investigate the demand for different levels of institutions that provide low to high levels of insurance and its subsequent impact on prosocial behavior. We conduct a large-scale online experiment where we add the possibility of purchasing insurance to safeguard against low reciprocity to the standard trust game. We compare two different mechanisms, the private (purchase) and the social (voting) choice of institutions. Whether voted or purchased, we find that there is demand for institutions in low trustworthiness groups, while high trustworthiness groups always demand lower levels of institutions. Lower levels of institutions are demanded when those who can benefit from opportunistic behavior, i.e. low trustworthiness individuals, can also vote for them. Importantly, the presence of insurance crowds out civic spirit even when subjects can choose the no insurance option: trustworthiness when formal institutions are available is lower than in their absence.
Keywords: C92; D02; D64; 330; institutions; trust; trustworthiness; voting; insurance